Retinopathy of prematurity in Africa: a systematic review. (4th July 2019) - Wang, Daniel; Duke, Roseline; Chan, Rv Paul; Campbell, J. Peter
ABSTRACT: Purpose : Retinopathy of prematurity (ROP) is widely regarded worldwide as a major cause of childhood blindness, however until recently the disease has not been recognized in most of the African continent. As a result of changing economic conditions, there is growing evidence that the population at risk for ROP in Africa is increasing. This report aims to summarize the published literature on ROP from Africa. Methods : We performed a systematic literature review of the English and French online literature databases by applying a general search strategy initially on May 1, 2017 with repeat inquiry on May 20, 2018. Search phrases included multiple variants of terms including "ROP", "retinopathy of prematurity", in conjunction with each of the individual 54 recognized sovereign African states. Findings : A total of 25 individual studies from six African nations were identified: South Africa (10), Egypt (7), Nigeria (4), with the nations of Sudan, Rwanda, and Kenya each having one respective study. Two countries (South Africa and Kenya) have developed national ROP policies for primary and secondary prevention. Summary : Review of the published literature suggests that ROP is emerging in Africa, however, there are published data from 6/54 (11%) African nations. Blindness from ROP is often preventable with appropriate primary and secondary prevention. This report provides compelling evidence that these efforts should be undertaken to implement and evaluate regionally appropriate ROP prevention programs in a growing number of African countries.